Development and characterization of an anti-rituximab monoclonal antibody panel. Issue 3 (3rd April 2018) - Tada, Minoru; Suzuki, Takuo; Ishii-Watabe, Akiko
ABSTRACT: During the development of monoclonal antibodies (mAbs) and other therapeutic proteins, immunogenicity, in particular the induction of anti-drug antibodies (ADAs), is an important concern, and thus immunogenicity assessment is a requirement for their approval. Establishment of appropriate methods for detecting and characterizing ADAs is necessary for immunogenicity assessment, but the lack of commonly available reference standards makes it difficult to compare and evaluate the methods. It is also difficult to compare the data with those obtained by other methods or facilities without reference standards. Here, we developed a panel of ADAs against anti-CD20 rituximab (Rituxan®, MabThera®); the panel consisted of eight clones of recombinant human-rat chimeric mAbs that target rituximab. The anti-rituximab mAbs showed different binding properties (specificity, epitope and affinity), and different neutralization potencies for CD20 binding, complement-dependent cytotoxicity and antibody-dependent cell-mediated cytotoxicity. The molecular size of the immune complex consisting of rituximab and the anti-rituximab mAb differed among the clones, and was well correlated with their level of Fcγ-receptor activation. These results suggest that the ADAs chosen for the newly developed panel are suitable surrogates for human ADAs, which exhibit different potential to affect the efficacy and safety of rituximab. Next, we used this panel to compare several ADA-detecting assays and revealed that the assays had different abilities to detect the ADAs with different binding characteristics. We conclude that our panel of ADAs against rituximab will be useful for the future development and characterization of assays for immunogenicity assessment.